The Effect of Using Plickers on Student Learning Outcomes and Perceptions in English Learning in Grade VI of MI Darul Ulum - arjul inayah; Syifa' Khuriyatuz Zahro; Buyun Khulel (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
English language instruction frequently encounters challenges related to low student engagement and unsatisfactory academic performance, especially when conventional teaching approaches lack interactivity. A potential solution to these issues involves integrating educational tools such as the Plickers application, which supports real-time interaction and immediate feedback. This study explores the effect of Plickers on student achievement and engagement in English learning among sixth-grade students at MI Darul Ulum. Utilizing a Classroom Action Research (CAR) approach in one cycle, the research included a pretest, the application of Plickers, a posttest, and student interviews. The findings demonstrated a significant improvement in students’ average scores, rising from 48.46 before the intervention to 85.38 afterward. Interview responses also revealed increased student interest and active participation during lessons involving Plickers, although some technical challenges were noted. The results suggest that Plickers is a valuable tool for enhancing both learning outcomes and student participation in English education.